Experimental study on natural fiber composites for strengthening of masonry - Codispoti, R. (2012)
In the present paper the first results obtained from a vast experimental investigation carried out on natural fiber composite materials (flax, hemp, jute, sisal and coir) are reported. Tensile tests on single yarns and fabrics have been carried out according to the current standards. Two types of matrices have been used: polymeric and mortar-based matrices. Therefore, the composites materials NFRP (Natural Fiber Reinforced Polymer) and NFRG (Natural Fiber Reinforced Grout) have been obtained. A new fiber placement technology has been studied, the so-called "braiding technology", in order to increase the mechanical properties of the natural non-impregnated materials. The results obtained, were compared with those of the most common composites systems (CFRP and GFRP).